The food effect on the pharmacokinetics of TQB3616 capsule in Chinse healthy subjects: a randomized, open-label, single-center, two-period, two-sequence crossover phase I clinical trial - Dai, Jun; Zhou, Yanan; Zhang, Lei; Ren, Qing; Liu, Zhengzhi; Wang, Yanli; Cheng, Yang; Deng, Qiaohuan; Yang, Haimiao; Zhang, Hong (Frontiers in Pharmacology, 2025)
PurposeThe purpose of this study was to evaluate the food effect on the pharmacokinetics of TQB3616 capsule in Chinse healthy subjects.MethodsThe subjects were randomly allocated to two distinct sequences in a 1:1 ratio. During each treatment periods, subjects ingested a single oral dose of 180 mg TQB3616 capsule administered with 240 mL of warm water under fasted and fed conditions. To avoid carryover effects, a 19 days washout period was strictly implemented between treatment periods. Blood samples were collected in accordance with the study protocol, and the plasma concentration of TQB3616 was measured using a fully validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. Safety evaluations were performed continuously throughout the duration of the trial.ResultsFollowing the administration of TQB3616 capsules under both fasted and fed conditions, the geometric mean ratios of Cmax, AUC0-t, and AUC0-∞ for TQB3616 in the fed state compared to the fasted state were 148.04%, 145.06%, and 143.13%, respectively. The corresponding 90% confidence intervals (CIs) were 101.23%–216.51%, 117.68%–178.83%, and 116.46%–175.91%, none of which fell within the conventional bioequivalence range of 80.00%–125.00%. A total of 81 adverse events (AEs) were reported among 16 subjects, with 77 events deemed related to the drug. Among the 77 drug-related adverse events, two cases were grade II, with the rest being grade I. Notably, there were no serious adverse events, deaths, or unexpected serious reactions.ConclusionA pharmacokinetic study conducted on healthy volunteers, who received a single 180 mg dose of TQB3616 capsules under fasting and fed conditions, demonstrated clinically significant effects of food on the drug’s bioavailability. Compared with fasted, postprandial administration delayed median Tmax by 1 h while increasing total systemic exposure and peak concentration. Additionally, postprandial dosing was associated with reduced incidence of gastrointestinal adverse reactions. These data support the recommendation that TQB3616 capsules be administered with food to maximize therapeutic bioavailability while improving gastrointestinal tolerability profile.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn, identifier, CTR20210354; clinicaltrials.gov, identifier, NCT05344729.